A novel regeneration protocol for LA Lilium - Asmita, Asmita; Sindhu, S S; Jayanthi, M; Singh, M K; Dhiman, M R (The Indian Journal of Agricultural Sciences, 2020)
Lilium is a high value ornamental crop and its demand particularly LA hybrids is growing day by day. To utilize the high regeneration potential in Lilium, transverse thin cell layer sections were excised from in vitro bulb scales of LA Lilium hybrid cv. Brindisi and inoculated on MS medium with 3% sucrose, 0.8% agar and varied concentration of 6-BAP, NAA and 2,4-D. Results showed that Protocorm like Bodies (PLBâ€™s) were directly being induced from the surface of t TCL explant. These protocorm like bodies are unipolar structure forming shoot and further developed root when transferred to rooting medium. When NAA was fortified with 6-BAP in MS medium, its regeneration percentage was recorded maximum in the combination 6-BAP (2 mg/l) and NAA (0.50) mg/l), whereas, maximum number of adventitious shoots per explant were recorded in 6-BAP (3 mg/l) and NAA (0.50) mg/l). Although, adventitious shoot buds were also produced on hormones free medium but at a very slow rate. The regeneration percentage was enhanced in the presence of NAA as compared to 2, 4-D when supplemented with 6-BAP. The regenerated bulblets were best rooted in IBA supplemented with Â½ MS medium and hardened in the glass jar.